A Show of Ewald's Law: I Horizontal Semicircular Canal Benign Paroxysmal Positional Vertigo - Zhang, Xueqing; Bai, Yanru; Chen, Taisheng; Wang, Wei; Han, Xi; Li, Shanshan; Liu, Qiang; Wen, Chao (Frontiers in Neurology, 2021)
Objective To evaluate horizontal semicircular canal effects according to Ewald’s law and nystagmus characteristics of horizontal semicircular canal benign paroxysmal positional vertigo (HSC-BPPV) in the supine roll test. Methods Patients with HSC-BPPV (n = 72) and healthy subjects (n = 38) were enrolled. Latency, duration, and intensity of nystagmus elicited by supine roll test were recorded using video nystagmography. Results In patients with HSC-BPPV, horizontal nystagmus could be elicited by right/left head position (positional nystagmus) and during head-turning (head-turning nystagmus), and nystagmus direction was the same as that of head turning. Mean intensity values of head-turning nystagmus in HSC-BPPV patients were (44.70±18.24)°/s and (44.65±19.27)°/s on the affected and unaffected sides, respectively, which was not a significant difference (p = 0.980), while those for positional nystagmus were (40.81 ± 25.56)°/s and (17.69 ± 9.31)°/s (ratio, 2.59 ± 1.98:1), respectively, representing a significant difference (p < 0.0001). There was no positional nystagmus in 49 HSC-BPPV patients after repositioning treatment, nor in the 38 healthy subjects. No significant difference in head-turning nystagmus was detected in HSC-BPPV patients with or without repositioning. Conclusions The direction and intensity of nystagmus elicited by supine roll test in patients with HSC-BPPV, was broadly consistent with the physiological nystagmus associated with a same horizontal semicircular canal with single factor stimulus. Our findings suggest that HSC-BPPV can be a show of Ewald's law in human body.